2022
DOI: 10.3389/fpubh.2022.872100
|View full text |Cite
|
Sign up to set email alerts
|

Bullying Experiences, Depression, and the Moderating Role of Resilience Among Adolescents

Abstract: IntroductionResilience refers to the ability to adapt to difficult situation or adversity. Resilience is what gives people the psychological strength to cope with stress and hardship. Previous studies have investigated the relationship between resilience and bullying victimization and mental health problems. But whether the moderating effect of resilience against depression varies among victims of different types of bullying victimization remains unknown.MethodsThe study used data from the Taiwan Adolescent to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…18 Some empirical evidence directly indicates the mediating role of resilience in the relationship among various negative factors, such as fear of COVID-19, envy, bullying experiences, and depression. [28][29][30] Resilience framework theory suggests that low psychological resilience interacting with environmental factors might influence an individual's adaptation ability and possibly induce depression. 31,32 Overall, based on the existing hypothesis of interpersonal sensitivity affecting depression, we propose that resilience partly mediates the influence of interpersonal sensitivity on depression.…”
Section: Mediating Role Of Resiliencementioning
confidence: 99%
See 1 more Smart Citation
“…18 Some empirical evidence directly indicates the mediating role of resilience in the relationship among various negative factors, such as fear of COVID-19, envy, bullying experiences, and depression. [28][29][30] Resilience framework theory suggests that low psychological resilience interacting with environmental factors might influence an individual's adaptation ability and possibly induce depression. 31,32 Overall, based on the existing hypothesis of interpersonal sensitivity affecting depression, we propose that resilience partly mediates the influence of interpersonal sensitivity on depression.…”
Section: Mediating Role Of Resiliencementioning
confidence: 99%
“…Our finding from the mediating model supported the hypothesis that resilience negatively mediated the relationship between interpersonal sensitivity and depression, consistent with previous studies. [28][29][30] People with high interpersonal sensitivity levels are cautious and show low self-esteem in interpersonal relationships. 37 They may encounter more difficulties in interpersonal communication and underperform in handling dilemmas.…”
Section: The Mediating Role Of Resilience and The Moderating Role Of ...mentioning
confidence: 99%
“…They suggested that parents and academics regulate the digital behavior of adolescents and guide them to use the internet better. Lin et al ( 2022 ) indicated that people with higher resilience scores are well protected against depression resulting from cyberbullying victimization. Hence, studies clearly showed the importance of studying individual-level interventions to protect against cyberbullying and resulting mental issues.…”
Section: Resultsmentioning
confidence: 99%
“…Participants rated the items on a five-point Likert scale (0 = never; 1 = 1-2 times; 2 = about once a week; 3 = 2-3 times a week; 4 = more often) to report their bullying experience (included three main traditional bullying type in China: physical, verbal, and relational bullying) in school during the last 6 months (last semester, before the flood disasters begin). As many studies have used categorical variables to measure bullying victimization, the procedures of previous studies were followed to make the results of this study comparable with those of previous studies (Guy et al, 2017;Husky et al, 2020;Lin et al, 2020;Eyuboglu et al, 2021;Hysing et al, 2021;Lin et al, 2022). Responses were recorded as 0 (rated 0, no response) or 1 (Hong and Espelage, 2012;Hymel and Swearer, 2015;Hysing et al, 2021;Xue et al, 2022).…”
Section: Bullying Victimizationmentioning
confidence: 93%